CARACTERIZAÇÃO DOS PROJETOS FINALISTAS DE QUÍMICA DA REDE FEDERAL DE ENSINO NA FEIRA BRASILEIRA DE CIÊNCIAS E ENGENHARIA-FEBRACE (2010 A 2021) - FREDERICO FERREIRA MARTINS (2023)
Science Fairs play a fundamental role in the scientific development of young students. Through Fairs, teaching institutions, professors and students can dialogue with teaching, research and extension. Science Fairs, especially the Brazilian Science and Engineering Fair, are capable of stimulating and disseminating scientific culture among primary and secondary school students. In this context, the Federal Institutes of Science and Technology Education, created in 2008, with the objective of providing, as a priority, technical education at secondary level with a focus on Teaching, Research and Extension, emerges as an institution capable of developing Science Fair projects. This aptitude is due to the fact that the Campi have a staff of teachers with specific training, well-equipped laboratories and resources destined to the participation in events. In this way, the present work aimed to analyze the representativeness of the Federal Institutes in relation to the finalist Chemistry projects of FEBRACE between the years 2010 to 2021, making a quantitative survey of the number of finalist projects, identifying the most recurrent keywords and creating a platform that contains all data and summaries related to Chemistry at FEBRACE. This study was developed using bibliographic research and qualitative research. As bibliographic characteristics, books, articles and magazines were consulted, which gave basis to the research carried out, since the theoretical material apprehended in the bibliographic phase guided the qualitative incursions. Based on the data collected and treated, it was evident that the Federal Institute is the largest participant in FEBRACE in relative numbers, when taking into account the number of existing units in relation to other education networks. This shows us that investment in education aimed at meeting local productive arrangements and based on teaching, research and extension contributes a lot to awakening young people to scientific work, observing, creating hypotheses, testing, collecting data, discussing results and reaching conclusions about a given phenomenon.